PLASMA Î²-SECRETASE1 (BACE1) LEVELS AS MARKER OF COGNITIVE FUNCTION DECLINE IN ELDERLY - Syahfira A Syahna; Muhammad Ichwan; Nuraiza Meutia; Jelita Siregar; Zulham Yamamoto; Zulham Yamamoto (International Journal of Ecophysiology, 2023)
BACE1 which forms amyloid plaques consisting of amyloid Î² peptides is a typical neuropathological lesion in the brain of Alzheimer's disease. Many studies have shown that Î²-amyloid is central to the pathophysiology of Alzheimer's disease and may play an early role in neurodegenerative disorders. The BACE1 enzyme forms amyloid Î² plaques. The BACE1 protein is detectable in plasma and its levels are significantly increased in patients with mild cognitive impairment and future Alzheimer's. This AÎ² peptide accumulates into senile plaques causing the characteristics of Alzheimer's disease, can cause neuronal death and cognitive decline